Limitations of recellularized biological scaffolds for human transplantation. (22nd December 2019) - Bilodeau, Claudia; Goltsis, Olivia; Rogers, Ian M.; Post, Martin
Abstract: A shortage of donor organs for transplantation and the dependence of the recipients on immunosuppressive therapy have motivated researchers to consider alternative regenerative approaches. The answer may reside in acellular scaffolds generated from cadaveric human and animal tissues. Acellular scaffolds are expected to preserve the architectural and mechanical properties of the original organ, permitting cell attachment, growth, and differentiation. Although theoretically, the use of acellular scaffolds for transplantation should pose no threat to the recipient's immune system, experimental data have revealed significant immune responses to allogeneic and xenogeneic transplanted scaffolds. Herein, we review the various factors of the scaffold that could trigger an inflammatory and/or immune response, thereby compromising its use for human transplant therapy. In addition, we provide an overview of the major cell types that have been considered for recellularization of the scaffold and their potential contribution to triggering an immune response.